2021
DOI: 10.1177/20552076211019900
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of older adults with chronic disease on the use of wearable technology and video games for physical activity

Abstract: Background There is increasing interest in technology to deliver physical rehabilitation and allow clinicians to monitor progress. Examples include wearable activity trackers and active video games (AVGs), where physical activity is required to play the game. However, few studies have explored what may influence the effectiveness of these as technology-based physical activity interventions in older adults with chronic diseases. Objective This study aimed to explore: 1) perceptions about wearable physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 85 publications
(118 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, measures suggested to meet the individualized needs of COPD patients include regular assessment of the degree of respiratory difficulty, balance control ability, and osteoporosis status [ 55 57 ]; sharing activity data with participants using activity trackers [ 58 , 59 ]; utilizing new technologies for systematic and long-term risk monitoring [ 60 ]; encouraging female and comorbid patients to participate in PA programs [ 61 , 62 ]; providing online peer support or digital social interventions for younger participants [ 63 ]; and paying attention to the acceptance of patient role behavior in Asian culture, along with providing psychological care [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, measures suggested to meet the individualized needs of COPD patients include regular assessment of the degree of respiratory difficulty, balance control ability, and osteoporosis status [ 55 57 ]; sharing activity data with participants using activity trackers [ 58 , 59 ]; utilizing new technologies for systematic and long-term risk monitoring [ 60 ]; encouraging female and comorbid patients to participate in PA programs [ 61 , 62 ]; providing online peer support or digital social interventions for younger participants [ 63 ]; and paying attention to the acceptance of patient role behavior in Asian culture, along with providing psychological care [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The chronic conditions of WAT users were not a focus of the present study, despite such conditions being shown to affect WAT use in other studies [ 11 , 41 , 84 , 85 , 86 ], because most of the participants did not have chronic conditions that might limit their use of WAT, such as arthritis or chronic obstructive pulmonary disease, which have been associated with a lower likelihood of long-term use [ 41 , 84 , 85 , 86 ]. Similarly, a review of randomized controlled trials evaluating WAT interventions [ 11 ] showed that participants with chronic respiratory or cardiovascular diseases had significantly smaller increases in PA than did populations with other chronic conditions.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, AVGs were the most common form of gamification practice (58/70, 83%). AVGs are video games that require players to use a certain part of their body as a controller to interact with the game system [13,27]. They can be used as apps for smartphones, tablets, and desktops as well as in combination with hardware facilities such as game joysticks, electronic displays, robots, and VR technology to present AVG content.…”
Section: Technical Supportmentioning
confidence: 99%
“…In this review, some studies (31/70, 44%) indicated that relevant theories or concepts guided their gamification practices in the self-management of patients with chronic diseases. A total of 37 concepts or theoretical frameworks were mentioned in the included articles, most of which originated from psychology and cross-disciplinarity (n=33, 89%), such as self-determination theory [38,40,[42][43][44], flow theory [33,[45][46][47][48][49], social cognition theory [27,[50][51][52], goal-setting theory [34,43], information-motivation-behavioral technology model of behavior change [32,43], intrinsic motivation [16,53], self-efficacy [17,45], persuasion system design model [54], inhibitory control [55,56], patient-reported outcome [32], co-design approach, and participatory design [57].…”
Section: Theoretical Supportmentioning
confidence: 99%